Degradação de matéria orgânica terrestre por microrganismos do rio Amazonas – Metagenômica e genômica populacional - Santos Júnior, Célio Dias (2018)
Microbes from Amazon river basin represent an unexplored biodiversity, with a huge metabolic potential. This ecosystem receives large amounts of terrestrial organic matter (OM), which promotes heterotrophic microbial growth. Microbial populations have been exposed for millennia to a complex OM derived from plants, and these communities must have developed metabolic pathways to degrade it. In the present work, 106 metagenomes from 30 sampling stations of rivers and lakes of the Amazon river basin were analyzed, covering the freshwater and coastal ocean areas. Using the gold standard techniques for assembly and gene prediction, the first gene catalog of freshwater microorganisms was generated, containing more than 3.7 million non-redundant genes, predominantly those of bacterial origin (35.73%). The present work comprises the hugest biodiversity ever sampled in Amazon river until now. As an auxiliary system, the AGSSY program was created to assist in the data mining of this catalog, proving to be fast and efficient in this process. The analysis of k-mers diversity suggests that these genes originate from local evolutionary processes. In addition, there is a stratification of the OM processing in the water column, possibly regulated by a sophisticated system of alternative carbon sources use, mainly based on tricarboxylates. The spatial structure of the OM processing genes suggests a zonation of lignin, cellulose and hemicellulose degradation. Using hybrid binning methods, taking into account contigs composition and abundance, it was possible to reconstruct 51 non-redundant population genomes. Through the analysis of them, it was possible to verify abundant endemic species belonging to Bacteria and Archaea, with a predominance of the Proteobacterium phylum (39%). Population genome analyzes, together with the gene catalog data, suggest a sophisticated priming model for the degradation of terrestrial OM in the Amazon River. Such a model would be based on the retroinhibition undergone by organisms that oxidize lignin, and in a community of microorganisms using alternative carbon sources that blocks this effect.